Analisis Pemberdayaan Potensi Siswa Melalui Model Self Directed Learning Pada Pembelajaran Pendidikan Agama Islam - Mariadi; Surawan; Monalisa (STIT Muhammadiyah Paciran Lamongan, 2022)
The young generation is the nation's best asset; therefore, the younger generation should be able to know and develop the potential that exists within them to build the nation's civilization and become superior leaders. This article is motivated by the author's concern for the potential of the younger generation that has not developed significantly. The purpose of this study is to examine the extent to which the concept of the SDL model in empowering the potential of students in PAI learning. The type of research used is library research. Meanwhile, the data collection techniques used were documentation in the form ofbooks, journal articles, internet, magazines, newspapers, and so on. In this study, it was found that the concept of the SDL model can empower the potential of students in PAI learning, because the SDL model causes students to have the initiative to learn independently and according to their learning style. The use of the SDL model is certainly inseparable from the role of parents and teachers. Therefore, both parents and teachers should provide various stimuli, in the form of motivation or appreciation for each process of student development.